LOCAL SCOURING AROUND PILE AND CURVED CHANNEL - Dantje K. Natakusumah; Dhemi Harlan; Sony Herdiansyah (GEOMATE Journal, 2019)
One of the destructive water force is scouring due to obstruction or alteration of its flow. Understanding the process is crucially necessary to be able to predict and anticipate scouring. FVCOM model is used in this study to simulate scouring on the pile and curved channel. FVCOM model calibrated with a previous experimental study on straight channel case, modeled curved channel to reveal its capability to capture secondary flow phenomenon, and modeled flow with a pile on a curved channel to reveal its pattern. This study is intended to reveal the scouring pattern on the pile and curved channel. FVCOM model is based on the finite volume method to solve Navier Stokes hydrodynamics, Meyer Peter Muller sediment transports, and Exner bed updates equations. FVCOM model has successfully captured flow behavior around the pile and curved channels such as downflow on upstream of the pile, wake vortex on downstream of the pile, and secondary flow on the curved channel. Pile and curved channel caused scouring in each case. Together, they make a scouring phenomenon even more. This is well proven in FVCOM simulation as the pile on curved channel scoured deeper compared to those on straight one.